Formal Learning in Informal Settings—Increased Physics Content Knowledge After a Science Centre Visit - Solis, Daniel H.; Hutchinson, David; Longnecker, Nancy (Frontiers in Education, 2021)
Over the past 50 years, the prevalence of interactives in museums and science centres has increased dramatically, with interactive learning proliferating around the world. With a current estimated visitation of 300 million people each year, free-choice learning through museums and related venues has become a major source of human learning over the course of a lifetime. While many studies of visitor experience have examined positive changes in affective components of learning, fewer have examined whether specific scientific content knowledge is included in what is learnt. This research investigated gains in content knowledge through informal science learning. Three surveys were conducted at the Otago Museum’s science centre (Dunedin, New Zealand) with visitors eight years and older. The main component of the survey included a brief “formal” content knowledge assessment in the form of a pre-post multiple-choice test, with a focus on physics concepts illustrated in the science centre. Self-reported examples of science learned during the visit and selected items from the Modes of Learning Inventory complement the data. In the pre-post test, prior knowledge was age and gender dependent, with younger visitors and females getting significantly lower scores. Notwithstanding, visitors to the science centre had an overall average of 13% more correct answers in the test after visiting, independent of age and gender. A learning flow diagram was created to visualise learning in the presence or absence of interactivity. As expected, interactivity was found to increase learning.